Role Clarification Processes for Better Integration of Nurse Practitioners into Primary Healthcare Teams: A Multiple-Case Study - Isabelle Brault; Kelley Kilpatrick; Danielle D’Amour; Damien Contandriopoulos; Véronique Chouinard; Carl-Ardy Dubois; Mélanie Perroux; Marie-Dominique Beaulieu (Nursing Research and Practice)
Role clarity is a crucial issue for effective interprofessional collaboration. Poorly defined roles can become a source of conflict in clinical teams and reduce the effectiveness of care and services delivered to the population. Our objective in this paper is to outline processes for clarifying professional roles when a new role is introduced into clinical teams, that of the primary healthcare nurse practitioner (PHCNP). To support our empirical analysis we used the Canadian National Interprofessional Competency Framework, which defines the essential components for role clarification among professionals. A qualitative multiple-case study was conducted on six cases in which the PHCNP role was introduced into primary care teams. Data collection included 34 semistructured interviews with key informants involved in the implementation of the PHCNP role. Our results revealed that the best performing primary care teams were those that used a variety of organizational and individual strategies to carry out role clarification processes. From this study, we conclude that role clarification is both an organizational process to be developed and a competency that each member of the primary care team must mobilize to ensure effective interprofessional collaboration.